1983
DOI: 10.1017/s031716710004511x
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern Electroretinogram in Optic Nerve Demyelination

Abstract: The pattern electroretinogram (PERG) is probably generated by the ganglion cell layer of the retina whose axons constitute the conductive fibres of the optic nerves. A study was undertaken of the PERG in a group of patients with clinically definite multiple sclerosis who had suffered optic nerve demyelination to assess the value of recording the PERG as a method for electrophysiological determination of optic nerve dysfunction. Pattern visual evoked potentials (PVEP) were simultaneously recorded, each eye bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…Some studies have suggested that the PERG can be altered while the flash ERG is unaffected in cases of optic nerve damage (8 -10), but contradictory evidence has suggested that PERG has little or no place in the study of optic nerve disease (11,12).…”
Section: A Historical and Technical Aspectsmentioning
confidence: 99%
“…Some studies have suggested that the PERG can be altered while the flash ERG is unaffected in cases of optic nerve damage (8 -10), but contradictory evidence has suggested that PERG has little or no place in the study of optic nerve disease (11,12).…”
Section: A Historical and Technical Aspectsmentioning
confidence: 99%
“…PERGs have been reported as abnormal in a variety of optic nerve diseases including optic neuritis (Kirkham and Coupland, 1983;Mashima and Oguchi, 1985), glaucoma (Wanger and Persson, 1985;Bobak et al, 1981;Trick, 1985), and PERG loss has been reported in a neurometabolic storage disease with macular cherry-red spots . Recently we reported that in a small group of insulindependent OP and PERG abnormalities were present in some who had normal fundus examinations and retinal photography (Coupland, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported by other authors (25,26) . On the other hand, Kirkham, Coupland (27) did not find differences between the PERG amplitudes in patients with MS related optic neuritis and normal controls and concluded that PERG did not satisfactorily reflect optic nerve dysfunction.…”
Section: Demyelinating Injuries Of the Optic Nervementioning
confidence: 94%